A Critique of the Chinese Radical Net-Philosophy Community - Zhongkai Qian; Ngai Pun (tripleC: Communication, Capitalism & Critique)
This article delves into the dynamics of the Chinese net-philosophy community, a unique digital and radical subculture where young enthusiasts engage with philosophical ideas outside of traditional academic frameworks. We examine how radical knowledge was produced, validated, and circulated within these net communities, focusing on the aestheticisation of knowledge and its impact on political engagement. This study reveals how alternative intellectual pursuit in a digitalised pile of debris, where form and style prioritise over substance, synchronising ideas and actions leads to the opposite of its progressive politics. Reviewing the aestheticisation and alienation of knowledge, we examine the recurrence of establishing authority and status and the implication of aesthetic hierarchies and performative politics on the net community’s capacity for meaningful political action. Ultimately, we argue that while the aestheticisation of knowledge acknowledged a broader post-millennial youth spiritual crisis, the net-philosophy community was marked by a depoliticisation of intellectual debates and the failure of political engagement in digital spaces.